Urinary incontinence and sleep complaints in community dwelling older adults - Neda Sadat Nazaripanah; Yadollah Abolfathi Momtaz; Farideh Mokhtari; Robab Sahaf (Sleep Science)
Background: Sleep disorder is associated with poor quality of life in old age. Therefore, it is imperative to identify contributing factors leading to sleep disorder. The current study aimed to examine the impact of urinary incontinence on sleep complaint after controlling for potential sociodemographic and health covariates. Materials and Methods: A cross-sectional study was conducted on a sample of 184 community dwelling older adults 60 years and older in Yazd, Iran, 2016. In order to obtain the sample a multistage proportional random sampling technique was employed. Sociodemographic characteristics, sleep complaint, and urinary incontinence were collected from medical records. Statistical analyses were performed using SPSS version 24. A multiple logistic regression analysis was used to examine the impact of urinary incontinence on sleep complaint after controlling for potential covariates. Findings: A total of 184 respondents with a mean age of 68.48±6.65 years (age range, 60-87 years) were included in the study. About 70% of the respondents were women, 72.8% were married, 68.5% were not formally educated, and 21.7% were living alone. The prevalence of sleep complaint and urinary incontinence were 27.2% (95% CI: 21-34) and 22.3% (95% CI: 17-29), respectively. The results of the multiple logistic regression analysis revealed respondents with urinary incontinence were four times more likely to suffer from sleep complaint than those without urinary incontinence after adjusting for potential covariates (AOR=4.04, 95% CI: 1.74-9.35, p<0.001). Conclusion: Based on the results of this present study, which showed that urinary incontinence independently contributed to sleep complaint among older adults, it is necessary to employ effective interventions for controlling urinary incontinence to reduce sleep complaints.